Analysis of Rifapentine for Preventive Therapy in the Cornell Mouse Model of Latent Tuberculosis - Miyazaki, Eishi (American Society for Microbiology, 1999)
Rifapentine is a long-acting rifamycin which may be useful for intermittent drug therapy against tuberculosis. In this study we measured the efficacies of rifapentine-containing intermittent drug regimens for preventive therapy using the Cornell mouse model of latent tuberculosis. We infected groups of mice intravenously with Mycobacterium tuberculosis and then treated them with isoniazid and pyrazinamide for 12 weeks according to the Cornell latency development protocol. After a 4-week interval of no treatment, experimental preventive therapy was administered by esophageal gavage for 12 or 18 weeks. After equilibration and dexamethasone amplification treatment, mouse organs were analyzed by quantitative colony counts to measure the effectiveness of therapy. Our results showed that once-weekly isoniazid plus rifapentine combination therapy for 18 weeks was an effective preventive regimen with sterilizing potency and bacillary load reduction comparable to those of daily isoniazid therapy for 18 weeks. Monotherapy with rifapentine weekly or fortnightly or with rifampin twice weekly for up to 18 weeks did not offer advantages in reducing bacillary load or in sterilizing organs compared to the effects of a placebo. These results with the Cornell mouse model indicate that once-weekly, short-course preventive therapy with isoniazid plus rifapentine is effective and may warrant investigation in humans with latent tuberculosis infection.